(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2013)
The present study was carried out to evaluate the effective concentration of ethanol extract of Feronia elephantum leaf and bark on male reproductive system of albino rats. The study was divided into four groups of five animals each. The first group (I) received distilled water for a period of 14 days, served as control. The groups II, III and IV of animals were administered the ethanol leaf extract daily at 400mg/kg body weight, bark extract daily at 400 mg/kg body weight and 1:1 ratio of leaf (200mg/kg b.wt) and bark (200mg/kg b.wt) extract of Feronia elephantum respectively for a period of 14days. Significant decreases in the weight of testis (p<0.05), epididymis (p<0.01) and seminal vesicle (p<0.05) were observed. The results of the hormonal assay showed that, increased serum levels of FSH and estrogen but decreases in the serum levels of LH and testosterone compared to control. The results showed that, Feronia elephantum has effects on male rat reproduction, affecting the sexual behavior and epididymal sperm concentration.